2012
DOI: 10.5038/1936-4660.5.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Literacy Interventions at University of Cape Town: Effects of Separation from Academic Disciplines

Abstract: The aim of the Numeracy Centre at the University of Cape Town is to develop students' quantitative literacy (QL) in a manner consistent with their programmes of study and intended roles in the community. Our theoretical perspective on the nature of QL is in line with that of the New Literacies Studies and sees academic QL as practices in different academic disciplinary contexts. This means that for us the ideal curriculum structure for developing QL would fully integrate it into the teaching of the disciplines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Spreadsheets are known to enhance quantitative reasoning and have been implemented in a variety of courses as noted in numerous papers in this journal (e.g., Steele and Kiliç-Bahi 2008, Gaze 2010, Vacher and Lardner 2010, Frith 2012, Lehto and Vacher 2012, Mayfield and Dunham 2015, Ricchezza and Vacher 2017.…”
Section: The Role Of Excelmentioning
confidence: 99%
“…Spreadsheets are known to enhance quantitative reasoning and have been implemented in a variety of courses as noted in numerous papers in this journal (e.g., Steele and Kiliç-Bahi 2008, Gaze 2010, Vacher and Lardner 2010, Frith 2012, Lehto and Vacher 2012, Mayfield and Dunham 2015, Ricchezza and Vacher 2017.…”
Section: The Role Of Excelmentioning
confidence: 99%
“…[1][2][3][4] Consequently, all medical schools have in recent years evaluated and adapted their selection criteria and processes. [5,6] Most South African (SA) medical schools use academic and non-academic criteria to select students, the former accounting for 70 -80% of admission requirements. [5] Some authors suggest that previous academic performances alone are not a fair reflection of some other very important characteristics required to be successful at medical school.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicated that many students lack quantitative concepts and techniques that medical courses appear to assume students have. [6] Although all medical students have studied MA at school, it does not necessarily mean that they are prepared for the QL demands of the curriculum. School MA does not include applying the mathematical techniques in real contexts and the statistical content of the school MA curriculum is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Steele and Kiliç-Bahi (2008), Bressoud (2009), andFrith (2012) speak to across-the-curriculum programs. Sweet et al (2008) discuss an example of courses specifically in sociology and communication using quantitative data retrieved from databases to stimulate student interests in class discussion, advance analytic skills, and develop capacities in written and verbal communication.…”
Section: Towards a Database Of Quantitative Databasesmentioning
confidence: 99%